Рентгеноспектральне дослідження електронної структури піровуглецю, одержаного карбонізацією толуілендиізоціанату в матриці високодисперсного діоксиду кремнію - Димарчук, В.О.; Огенко, В.М.; Набока, О.В.; Дубровіна, Л.В.; Зауличний, Я.В.; Хижун, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
The results of studies of the electronic structure and the surface chemical state of carbon-contai-ning porous materials derived by carbonization of toluylene-diisocyanate (TDI) in a matrix of fine silica are presented. It is established that products of TDI carbonization are fine spherical clusters (with their sizes less than 100 nm) that reveal a weak bonding with the SiO2 matrix. The surface of products of TDI carbonization on the SiO2 matrix possesses C−C, C−H, C−NHx, and COO groups.